Identifying causes of Pay Inequity : Exploring the role of organizational compensation practices and the EU Pay Transparency Directive in supporting pay equity - Hartikainen, Helene (My University, 2024)
The conversation on equal pay and gender pay equity has been on the table for a while now. Despite previous legislation and initiatives, the situation hasn’t been improving enough, creating a need for new legislative actions, and the EU Pay Transparency Directive coming into force in 2026 is only one of them. Previous research around the topic has been conducted on the effects of pay transparency on pay equity and the effects of pay transparency in organizations. The purpose of this thesis is to explore some of the underlying causes of pay inequity within organizations with a focus on their pay practices, as well as discover challenges and opportunities related to the EU Pay Transparency Directive in promoting pay equity. The research was conducted as qualitative research by means of semi-structured thematic interviews. A total of five in-depth interviews exploring the views and experiences of experts were conducted in March-April 2024. Underlying causes for pay inequity within organizations were identified on different levels, including a societal, individual, and organizational level, also influenced by the market dynamics. The identified organizational level causes were related to organization’s structures and attitudes, the culture, the capabilities of leaders and well as possible systemic biases. The importance of a company pay philosophy as well as a system for evaluating different roles were also highlighted, and furthermore seen to create a foundation for other compensation practices of organizations. The focus of this thesis was on the pay practices of organizations, and the specific compensation related practices and processes that were seen as critical in terms of pay equity, were identified as the practices of hiring and position changes, followed by those of salary reviews and performance management. As a conclusion, the existence of the right elements and systems is not enough to remove pay disparities – the practices and processes need to be both built to eliminate pay discrimination and used consistently across the organization. This is where the culture and leadership were also suggested to play a significant role. The EU Pay Transparency Directive was expected to bring new challenges to HR and organizational leaders. Some challenges were connected to building the role and pay structures, ensuring the needed resources for analysing pay data, as well as dealing with the communicational challenges and employee reactions. In addition, some question marks were still identified regarding the use of the directive, especially around what can in the end be considered as work of equal value and how to objectively prove it. Nevertheless, the directive was also believed to drive positive changes, such as pushing organizations to review and update their pay practices, providing clarity to both employees and managers in pay-related discussions, supporting the individual in career and pay development, and reducing the role of pay speculation, resulting in more equal pay internally and externally. As a conclusion from the whole research, the directive could support pay equity by bringing pay discussion and pay gap reporting out in the open. To truly promote pay equity and close the pay gaps in the long run, the underlying causes need to be identified and eliminated. Nevertheless, increasing awareness and understanding on pay inequities will support both organizations and the society towards more equal pay.

Tasa-arvoiseen palkkaan ja sukupuolten palkkatasa-arvoon liittyvää keskustelua on käyty jo jonkin aikaa. Aiemmista lainsäädännöistä ja aloitteista huolimatta tilanne ei ole kuitenkaan parantunut tarpeeksi, mikä on luonut tarpeen uusille lainsäädännöille: EU:n 2026 voimaan tuleva palkka-avoimuusdirektiivi on vain yksi niistä. Aiemmat tutkimukset ovat keskittyneet palkka-avoimuuden vaikutuksiin organisaatioissa sekä yhteyksiin palkka-avoimuuden ja palkkatasa-arvon välillä. Tämän opinnäytetyön tarkoituksena on tutkia organisaatioiden palkkaerojen taustalla vaikuttavia syitä keskittyen palkitsemiskäytäntöihin sekä selvittää EU:n palkka-avoimuusdirektiiviin liittyviä haasteita ja mahdollisuuksia palkkatasa-arvon edistämisessä. Tutkimus suoritettiin laadullisena tutkimuksena teemahaastattelujen avulla. Yhteensä viisi asiantuntijoiden näkemyksiä ja kokemuksia käsittelevää haastattelua pidettiin maalis-huhtikuussa 2024. Organisaatioiden palkkaerojen taustalla olevia syitä tunnistettiin yksilöllisellä, yhteiskunnallisella sekä organisaation tasolla, joihin myös markkinadynamiikkojen huomattiin vaikuttavan. Organisaatiotasolla tunnistetut syyt liittyivät organisaatioiden rakenteisiin ja asenteisiin, kulttuuriin, johtajien kyvykkyyksiin sekä mahdollisiin systemaattisiin vinoumiin. Yrityksen palkitsemisfilosofian ja eri roolien arvioimiseen tarkoitetun järjestelmän tärkeyttä korostettiin myös, ja niiden nähtiin myös luovan pohjan organisaatioiden muille palkitsemiskäytännöille. Tämän opinnäytetyön painopiste oli organisaatioiden palkitsemiskäytännöissä. Erityisesti palkkatasa-arvon kannalta kriittisimmiksi tunnistetut käytännöt ja prosessit olivat rekrytointiin ja tehtävän muutoksiin liittyvät käytännöt, joita seurasivat palkantarkistuskierrokset ja suorituksen johtamiseen liittyvät prosessit. Johtopäätöksenä todettiin myös, että oikeiden elementtien ja järjestelmien olemassaolo ei riitä palkkaerojen poistamiseen – käytäntöjen ja prosessien on oltava sekä rakennettu lieventämään palkkadiskriminaatiota että käytettyinä johdonmukaisesti läpi organisaatioiden. Tässä yhteydessä myös organisaatiokulttuurin ja johtajuuden nähtiin olevan merkittävässä roolissa. EU:n palkka-avoimuusdirektiivin odotettiin tuovan uusia haasteita HR:lle ja organisaation johtajille. Jotkin haasteet liittyivät rooli- ja palkkarakenteiden rakentamiseen, palkkatietojen analysoimiseen tarvittaviin resursseihin sekä viestinnällisten haasteiden ja työntekijöiden reaktioiden käsittelyyn. Lisäksi direktiivin käytöstä tunnistettiin vielä joitakin kysymysmerkkejä, erityisesti siitä, mitä lopulta voidaan pitää samanarvoisena työnä ja miten se voidaan objektiivisesti todistaa. Haasteista huolimatta direktiivin uskottiin ajavan positiivisia muutoksia, kuten organisaatioiden palkkakäytäntöjen tarkistamista ja päivittämistä, selkeyttä sekä työntekijöille että johtajille palkkaan liittyvissä keskusteluissa. Sen koettiin myös tukevan yksilön ura- ja palkkakehitystä sekä vähentävän tarvetta palkkaspekulaatioille, minkä taas nähtiin johtavan tasa-arvoisempaan palkkaan niin sisäisesti kuin ulkoisesti. Palkka-avoimuus voi tukea palkkatasa-arvoa tuomalla palkkakeskustelun ja palkkaerojen raportoinnin julkisuuteen. Palkkatasa-arvon todellinen edistäminen ja palkkaerojen umpeen kurominen vaatii kuitenkin pitkällä aikavälillä taustalla olevien syiden tunnistamista ja systemaattista poistamista. Siitäkin huolimatta palkkatasa-arvoon liittyvien kysymysten tietoisuuden ja ymmärryksen lisääminen tukee sekä organisaatioita että yhteiskuntaa kohti tasa-arvoisempaa palkitsemista.
Keywords: pay equity, pay transparency, EU Pay Transparency Directive, palkkatasa-arvo, palkka-avoimuus, EU palkka-avoimuusdirektiivi